2021
DOI: 10.3390/cli9030046
|View full text |Cite
|
Sign up to set email alerts
|

Climate Services for Renewable Energy in the Nordic Electricity Market

Abstract: To limit global warming to less than 2 °C requires a low-carbon transition with very large shares of renewables. Options such as wind, solar and hydro are influenced by both short and longer-term weather and climate variability. While still subject to natural and anthropogenic climate forcing and fluctuating energy prices, water reservoirs can dually operate as storage and production facilities and serve to balance the more volatile production capacity from solar and wind. This paper assesses the dynamics and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…These countries also have the fastest growth rate of RES in primary energy consumption. As Danish researchers have pointed out (Halsnaes et al, 2021), the Nordic energy system is currently dominated by renewables, primarily by hydropower, with the other part (about a third) coming from nuclear and fossil fuels. When compared to the rest of Europe, the Nordic countries possess renewable energy resources such as hydropower and bioenergy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These countries also have the fastest growth rate of RES in primary energy consumption. As Danish researchers have pointed out (Halsnaes et al, 2021), the Nordic energy system is currently dominated by renewables, primarily by hydropower, with the other part (about a third) coming from nuclear and fossil fuels. When compared to the rest of Europe, the Nordic countries possess renewable energy resources such as hydropower and bioenergy.…”
Section: Discussionmentioning
confidence: 99%
“…Nordic countries still have the potential to improve the management of existing resources. The planned increase in the share of renewable energy under the Paris Agreement will be particularly in wind power and, to a lesser extent, biomass, both of which are presumed to significantly increase the volatility of energy supply in Scandinavia, particularly in Sweden, as nuclear power is replaced (Halsnaes et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…A dynamical approach used for daily planning in an electricity market is introduced in Ref. [ 189 ]. The purpose of the online operational plan is to closely adhere to a predetermined production timeline.…”
Section: An Updated Review Of Frequency Control Techniques For Modern...mentioning
confidence: 99%
“…Accordingly, mitigation strategies are needed to protect the environment from adverse effects. Recent studies have found under-utilized potential in the renewable energy sector that could be achieved by considering better climate services such as the seasonal forecast of inflow (Halsnaes et al 2021). As hydropower is the dominant renewable energy source in the region, continued collaboration between hydrologists and the energy sector will be essential for a sustainable future through the sustainable operation and effective utilization of resources.…”
Section: River Regulation and Flood Controlmentioning
confidence: 99%